Reorientasi Pendidikan Agama Di Sekolah - Zainuddin, M. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2003)
It is not false to be said that the history of civilization is the history of human being, because in the reality, human being is the civilized creature that has ethics. Therefore, he needs education and teaching to make himself mature and developed, but he must get religious education to make himself mature. In other words, the importance of religion is not merely the letters compiled into law, but, the spirit of its religion, namely faith and affection is more important. Through that education, it is expected that the learners will have ideal personality, high solidarity, honesty, justice, harmony and get far from disintegration, violence, conflict and tension among the followers of religion.